Produção biotecnólogica de ácido succínico a partir de casca de arroz - Bevilaqua, Daiane Balconi (2013)
Rice husk is a subproduct of the food industry, rich in carbohydrates, which can be partially fractionated and converted into fermentable sugars. In this work, it was investigated the best conditions for the conversion of the residual biomass, rice husks, into succinic acid, an important start molecule for the synthesis of the chemo-pharmaceutical industry. With the goal of the separation of lignin and transformation of cellulose and hemicellulose into sugars, the rice husks were submitted, initially, to acid hydrolysis, in autoclave and in pressurized polytetrafluoroethylene reactor. The hydrolysis conditions were optimized by factorial design for the pressurized acid hydrolysis; temperature, time and acid catalyst concentration (HCl or H2SO4) were evaluated. For the acid hydrolysis in autoclave, it was optimized the ratio rice husks mass: acid volume, time and concentration of HCl or H2SO4. It was observed that the sugar production by using autoclave was lower than by the pressurized hydrolysis system, needing further concentration of the hydrolysate for the subsequent fermentation step. The best results were obtained with the polytetrafluoroethylene reactor, by 59 bar, with HCl 0,26 mol L-1, at 175°C and reaction time of 46 min, yielding 19.0 g L- 1 of glucose and 3.01 g L- 1 of xylose. The efficiency of different detoxification methods of the hydrolyzed rice husk were evaluated; the combined method of pH adjustment plus adsorption on active carbon was the most effective by eliminating inhibitors, without appreciable reduction of the sugar concentration. The detoxified hydrolysate was sterilized and adjusted at pH 7 and fermented with A. succinogenes at 37 ° C, in anaerobic medium, occurring the conversion of the two main monosaccharides, glucose and xylose, into succinic acid. The nutrient concentration and the agitation rate of the medium were also optimized by factorial design. As a result, after 54 h of static fermentation, the hydrolysate was supplemented with 8.40 g L-1 yeast extract and 1.40 g L -1 of NaHCO3, to yield 59.9% succinic acid. Almost all of the sugar at this time was consumed and converted to succinic acid; at the same time, acetic and formic acid are formed, but, in low concentrations related to the production of succinic acid, not compromising the yield of the process. For the succinic acid extraction and purification, the fermentate was submitted to the solid phase extraction procedure; cartridges with different extraction phases were tested, and among them, the ion exchange one was the only effective, with recoveries up to 96%. After solid phase extraction, the eluted solution, containing 12.05 g L- 1 succcinic acid, was lyophilized, and crystals of succinic acid with 80.7% (m m- 1) were obtained. The raw material used in the bioprocess has no commercial value, representing a zero cost carbon source, which reveals itself adequate to the succinic acid production by fermentation with A. succinogenes, after hydrolysis. The use of the residual rice husk can contribute to the mitigation of the environmental impact resulting from the illegal discharge in the environment.